A regression model to determine load for maximum power output - Jandacka, D.; Vaverka, F. (Sports Biomechanics, 2008)
The aims of this study were to create a regression model of the relationship between load and muscle power output and to determine an optimal load for maximum power output during a countermovement squat and a bench press. 55 males and 48 females performed power testing at 0, 10, 30, 50, 70, 90, and 100% of their individual one-repetition maximum (1-RM) in the countermovement squat and bench press exercises. Values for the maximum dynamic strength and load for each lift were used to develop a regression model in which the ratio of power was predicted from the ratio of the load for each type of lift. By optimizing the regression model, we predicted the optimal load for maximum muscle power. For the bench press and the countermovement squat, the mean optimal loads for maximum muscle output ranged from 50 to 70% of maximum dynamic strength. Optimal load in the acceleration phase of the upward movement of the two exercises appeared to be more important than over the full range of the movement. This model allows for specific determination of the optimal load for a pre-determined power output.